On the Iranian English as Foreign Language Novice and Experienced Teachers’ Attributional Styles and Professional Identity - Kalali Sani, Seyed Farzad; Motallebzadeh, Khalil; Khodabakhshzadeh, Hossein; Zeraatpisheh, Mitra (Frontiers in Psychology, 2022)
Teacher professional identity is a characteristic of a teacher, which should be developed in a long, continuous, and ongoing process and usually happens in contextual settings. In addition to several factors influencing Teacher Professional Identity (TPI), such as university education and empowerment courses, experience seems to play a significant role. Moreover, the role of psychological factors is highly undeniable in formation and development of TPI. Attributional style is defined as the consistent way by which people can explain the reasons of occurrence of good or bad events. Besides considering attributional styles as one of the crucial variables for academic success, it can be regarded as one of the aspects of shaping one's identity in general and the teacher's identity in particular. In order to study the relationship between teachers’ attributional style and teacher professional identity regarding their experience, two questionnaires were distributed among 317 Iranian EFL teachers, and about 80% returned them. The researchers ran correlational analyses and the results revealed that there was a positive and significant relationship (p=.04) between teachers’ TPI and Teacher Attributional Styles (TAS). Moreover, experienced teachers proved to have a significant difference with novice teachers regarding their TPI. The findings of this study would hopefully be advantageous for teachers educators to form pre-service teachers by ways of constructing identity, and they may be applicable for Iranian EFL teachers to know and focus on different aspects of their professional identity and how to control the influencing factors and shape and empower PI in different domains, such as teaching experience, by means of exploring and knowing their attributional styles.